2013
DOI: 10.1097/mbc.0b013e32835a0850
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of mean platelet volume for predicting stroke risk in atrial fibrillation patients

Abstract: Early detection of atrial fibrillation patients at high risk for stroke is important. There are some studies which indicate that mean platelet volume (MPV) determines the prognosis and risk in patients with a stroke. In this study, our aim was to investigate the association between the MPV measured in stroke patients with atrial fibrillation. Consecutive patients referred to our center between January 2010 and April 2012 were included in this study. The patients with atrial fibrillation were classified into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
3
21
1
1
Order By: Relevance
“…The association of high level of thrombin generation parameters with a high mean platelet volume, which is a recognized independent risk factor for stroke in patients with atrial fibrillation 23 , or with the presence of microparticles which simultaneously express CD62E and CD41 in Ph-negative MPN patients could be other aims for future thrombotic risk studies.…”
Section: Resultsmentioning
confidence: 99%
“…The association of high level of thrombin generation parameters with a high mean platelet volume, which is a recognized independent risk factor for stroke in patients with atrial fibrillation 23 , or with the presence of microparticles which simultaneously express CD62E and CD41 in Ph-negative MPN patients could be other aims for future thrombotic risk studies.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 There is a positive association between MPV and the severity of acute ischemic stroke 23 and in predicting the risk of ischemic stroke in patients with atrial fibrillation. [24][25][26] Butterworth and Bath 27 reported that platelet volume is increased in patients with acute ischemic stroke. O'malley et al 28 reported high values of MPV in all subtypes of ischemic stroke.…”
Section: Mean Platelet Volume Predictor Of Stroke Riskmentioning
confidence: 99%
“…The relationship between increased platelet activity and atherosclerotic disease, including stroke, has been well documented [6][7][8]. It has been shown that high MPV is associated with an increased risk of stroke [9] and is an independent risk factor for stroke [10] in patients with atrial fibrillation. Furthermore, in a previous study Kim et al [11] showed that left atrium diameter is an independent predictor of stroke in patients without atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%